Chemical Analysis of Ground Waters in Tabriz Area, Northwestern Iran - Mehrdadi, N.; Baghvand, A.; Etemadi, H.; Razmkhah, Navid; Esmaeili Bidhendi, M. (Asian Journal of Chemistry, 2010)
Hydrochemical investigations were carried out in Tabriz area, northwestern Iran, to assess the chemical composition of groundwater. The area falls in a semi-arid type of climate. In this area, groundwater has been exploited over the past century. A total of 26 representative groundwater samples were collected from different wells to monitor the water chemistry of various ions. Water presents a large spatial variability of the chemical species (Na-SO4, Na-Cl, Mg-HCO3, Na-HCO3 and Ca-Cl) which is in relation to their interaction with the geological formations of the basin and evaporation. The hydro chemical types Na-SO4 and Na-Cl dominate the largest part of the studied area. All the samples in the studied area falls under the category of medium sodium hazard and in high salinity zone. Such water shouldn't be used for plants and special management for salinity control is required.